2022
DOI: 10.1007/s00406-022-01388-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the cross-trait effects of the FOXP2 GWAS hit on clinical and brain phenotypes in adults with ADHD

Abstract: The Forkhead box P2 (FOXP2) encodes for a transcription factor with a broad role in embryonic development. It is especially represented among GWAS hits for neurodevelopmental disorders and related traits, including attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder, neuroticism, and risk-taking behaviors.While several functional studies are underway to understand the consequences of FOXP2 variation, this study aims to expand previous findings to clinically and genetically related phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…In a previous GWAS analysis, FOXP2 has been confirmed to be associated with neck or shoulder pain, and multi-site chronic pain (Johnston et al 2019; Meng et al 2020). In addition, FOXP2 has been found to be associated with the development of attention deficit hyperactivity disorder and psychological disorders (Wendt et al 2018; Meyer et al 2023). The identified brain regions, including the hypothalamus, are known to play crucial roles in central neuroendocrine and hormone secretion (Markakis 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous GWAS analysis, FOXP2 has been confirmed to be associated with neck or shoulder pain, and multi-site chronic pain (Johnston et al 2019; Meng et al 2020). In addition, FOXP2 has been found to be associated with the development of attention deficit hyperactivity disorder and psychological disorders (Wendt et al 2018; Meyer et al 2023). The identified brain regions, including the hypothalamus, are known to play crucial roles in central neuroendocrine and hormone secretion (Markakis 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The rs5886709 SNP selected from FOXP2 gene was associated with ADHD risk in a GWAS meta-analysis (Demontis et al , 2019). In another GWAS study conducted with adults with ADHD, it was reported to be associated with impulse control and decision-making mechanisms, although it was not specifically associated with ADHD status (Meyer et al , 2022). As far as we know, there has been no study comparing the specific cognitive functions for both psychopathologies of ADHD and SLD, including the studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in humans, FOXP2 has been implicated in various neuropsychiatric disorders such as autism spectrum disorder, attentiondeficit hyperactivity disorder (ADHD), and schizophrenia (e.g. Co et al, 2020;Demontis et al, 2019;Konopka and Roberts, 2016;Li and Pozzo-Miller, 2020;Meyer et al, 2022;Mukamel et al, 2011;Walker et al, 2012). These disorders may result from dysfunctional neuronal networks caused by disruptions in the interaction between FOXP2 and its transcription targets.. FOXP2 regulates the transcription of numerous downstream target genes (den Hoed et al, 2021;Konopka et al, 2012;Spiteri et al, 2007).…”
Section: Introductionmentioning
confidence: 99%